New Renewable Energy for Bali Tourist Destination: Potential and Challenges - Yasa, I Wayan Sugara; Suriana, I Wayan; Sukadana, I Wayan (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This research aims to explore potential and challenges of new renewable energy in Bali, which is a popular international tourist destination. Research methods: The research is based on several existing sources, both from daily news and existing articles regarding several renewable energy potentials in Bali. Almost all of the data is secondary data obtained from various agencies in Bali. The data are analyzed using qualitative analysis technique. Results and discussion: Economic growth and the very rapid number of tourist visits to Bali are driving problems in the energy sector. The potential for developing new renewable energy in Bali is very large, such as sunlight, wind and geothermal resources. In this case there are several challenges such as limited land, electricity grid integration, technology and costs, permits and regulations, public awareness, and the influence of weather. Implications: Collaboration between government, private sector, and society is needed to find the right solution. There is a need for a comprehensive action plan and appropriate policy support to accelerate the transition to renewable energy in Bali as an international tourist destination.